ISLAMIC EDUCATION VALUES CONTAINED IN UPIN AND IPIN ANIMATION SERIES OF RAMADHAN EPISODE - Mardianto Mardianto; Baihaki Harahap (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2020)
This study aims to determine what Islamic educational values are contained in the Upin and Ipin cartoons during the Ramadan episode. This research is a library research (library research). The method used to collect data is the documentation method. Analysis of the data that researchers use is content analysis, namely research conducted on information, which is documented in recordings, both in pictures, sounds and writings. Then a descriptive interpretation is carried out by providing an overview and interpretation as well as a description of the data that has been collected . The results of this study indicate that Upin and Ipin cartoons on the episode of the Ramadan theme have educational values contained therein. The educational values contained in the Upin and Ipin cartoon episodes of the theme of Ramadan include: First, the values of religious education which include, mahdhah worship and the value of social worship education kemasarakatan. Second, universal education values include, peace, respect, love, tolerance, responsibility, happiness, cooperation, honesty, humility, freedom, simplicity, unity